The Effect Of Liquidity On Liabilities: An Application In Automotive Companies - DAYI, Faruk; ÇETİNKAYA, Reşit (Journal of the Human and Social Sciences Researchers, 2019)
Liquidity refers to the ability of an enterprise to pay off its short or long term liabilities. The higher the profit of companies, the more the liquid assets. The sales, and consequently the profits of automotive companies operating in Turkey have been increasing in the last few years. Liquidity is expected to increase with the increase of profits. The aim of the study is to investigate the correlation between solvency and liquidity of automotive companies. In the application, the eight-year (2010-2017) financial statement data of 11 automotive companies operating in the Istanbul Stock Exchange (Turkey) were used. A panel data analysis was conducted using financial leverage ratio, cash, receivables, inventories, liabilities and revenue variances obtained from the financial statement data. It was determined that automotive companies had 54 percent of their assets in debts. As a result of the analysis, it was determind that there was a positive correlation between financial leverage ratio and receivables, liabilities and inventories, whereas there was a negative correlation between financial leverage ratio and revenues and liquid assets.
Keywords: Finans; Liquidity; Financial Leverage; Working Capital; Automotive Sector; Finance; Finance; Likidite; Finansal Kaldıraç; Çalışma Sermayesi; Otomotiv Sektörü; Finans; 9. Industry and infrastructure; 8. Economic growth; 1. No poverty; 12. Responsible consumption